(untitled) (CAHIERS MAGELLANES-NS, 2024)
Mobile commerce (m commerce) has revolutionized the landscape of electronic commerce (ecommerce) by leveraging mobile devices to facilitate seamless shopping experiences. This paper explores the pivotal role of M-commerce in transforming traditional online shopping practices. Key contributions include enhanced accessibility, convenience, and personalized user experiences, thereby expanding market reach and driving consumer engagement. The integration of M-commerce with social media platforms and advanced technological features has further accelerated its impact, fostering innovation in payment methods and data driven marketing strategies. As mobile technology continues to evolve, the influence of M-commerce on ecommerce trends is poised to grow, shaping future paradigms of digital retail.